In the shadow of Korematsu : democratic liberties and national security - Yamamoto, Eric K., 1952- (New York, NY : Oxford University Press, 2018)
The national security and civil liberties tensions of the World War II mass Japanese American internment (incarceration) link 9/11 and the 2015 Paris-San Bernardino attacks to the era in America darkened by accelerating discrimination against and intimidation of those asserting rights of freedom of religion, association, and speech, and one marked by increasingly volatile protests against racial and religious discrimination. This text discusses the broad civil liberties challenges posed by these past-into-the-future linkages, highlighting pressing questions about the significance of judicial independence for a constitutional democracy committed both to security and to the rule of law.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 5, 2018).
Keywords: Japanese Americans -- Legal status, laws, etc; Japanese Americans -- Civil rights; Japanese Americans -- Evacuation and relocation, 1942-1945.; Korematsu, Fred, -- 1919-2005 -- Trials, litigation, etc; Civil rights -- United States; National security -- United States; Law; International law